The Development of Digital Leadership Indicators of School Administrators under the Secondary Educational Service Area Office in the Northeastern Region - Kumhangphol, Naraporn; Srijumnong, Jutamas; Bangwiset, Suchat (Arts of Management Journal, 2024)
The objectives of this study were to: firstly, establish indicators for digital leadership among school administrators in the secondary educational service area office of northeastern Thailand; and secondly, assess how well the structural model of digital leadership aligned with empirical data in the same region. The research was carried out in three phases. Phase one involved constructing and refining digital leadership indicators through the analysis of existing research and documentation, expert interviews, and the creation of a conceptual framework. Phase two focused on evaluating the proposed model by comparing it to empirical data collected from a sample of 660 school administrators using statistical software. Data was gathered through a 5-level rating scale. In the third phase, the study investigated the application of the developed indicators to digital leadership. A quality assessment was performed by five experts using Likert’s 5-level rating scale questionnaire to evaluate the implementation of digital leadership indicators. The results of the study can be summarized as follows: The development of digital leadership indicators led to the identification of four main components, 12 sub-components, and 56 indicators for school administrators under the secondary educational service area office. The four main components were digital vision, digital literacy, digital communication, and digital culture. Each component included three sub-components and 14 indicators. The examination of the confirmatory factor analysis model demonstrated consistency with the statistical values: 2 = 22.35, DF = 23, GFI =0.99, AGFI =0.98, CFI = 1.00, SRMR =0.00, and RMSEA = 0.00. These results indicated that the model of digital leadership for school administrators aligns well with the empirical data, confirming the hypotheses.